2023
DOI: 10.2340/17453674.2023.9411
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of robotic-assisted versus conventional total knee arthroplasty: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background and purpose: Robotic-assisted total knee arthroplasty (RATKA) is an alternative surgical treatment method to conventional total knee arthroplasty (COTKA) that may deliver better surgical accuracy. However, its impact on patient outcomes is uncertain. The aim of this systematic review of randomized controlled trials (RCTs) is to evaluate whether RATKA could improve functional and radiological outcomes compared with COTKA in adult patients with primary osteoarthritis of the knee.Methods: We searched O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Respecting the patients' specific knee may help to increase clinical and functional outcomes. Potentially less revision surgery can be expected considering the fact that stiffness and instability as one of the main causes in up to 44% of these cases [15,20]. Robotic arm-assisted surgery helps to achieve the desired bone cuts and target limb alignment, along with symmetrically balanced flexion and extension gaps calculated intraoperatively [3].…”
Section: Discussionmentioning
confidence: 99%
“…Respecting the patients' specific knee may help to increase clinical and functional outcomes. Potentially less revision surgery can be expected considering the fact that stiffness and instability as one of the main causes in up to 44% of these cases [15,20]. Robotic arm-assisted surgery helps to achieve the desired bone cuts and target limb alignment, along with symmetrically balanced flexion and extension gaps calculated intraoperatively [3].…”
Section: Discussionmentioning
confidence: 99%
“…But there are also many studies reporting that RATKA has higher accuracy of bone cuts and implant alignment. 11,12 Ruangsomboon et al 34 reported that although RATKA likely results in higher radiologic accuracy than manual TKA, there is probably no clinically important difference in clinical outcomes between RATKA and manual TKA. One of the reasons for the different conclusions is that the occurrence of surgical errors is becoming lower and low as the experience of the surgeon accumulates, and a relatively small sample size might affect the results, as a result, a larger sample study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In einem kürzlich veröffentlichten Review mit Metaanalyse lässt sich durchaus ein Vorteil für die Robotik im Vergleich zur manuellen Knieprothesenimplantation darstellen [38]. Eine andere aktuelle Metaanalyse findet allenfalls einen minimalen klinischen Vorteil in Bezug auf den WOMAC-Score und die postoperative Beweglichkeit [41]. Allerdings handelt es sich hierbei um wenige Studien, kleine Patientenzahlen und wenige untersuchte Parameter.…”
Section: Take Home Messageunclassified